Under-Pricing and Undervaluation of PSUs' Shares in Disinvestment Programme: A Study - Mahajan, Shrikrishna (Indian Journal of Finance, 2007)
As the new economic policy (liberalisation-privatisation-globalisation-policy) has been adopted as a part of economic stabilization and structural adjustment programme (S&SAP) in 1991, the disinvestment has started in public sector as a route of privatization. The review of literature on privatization and disinvestment reveals that there are some issues that should be critically overviewed and it needs to suggest the remedies for their problems. One of these important issues is under-pricing and undervaluation of PSUs' shares in disinvestment programme in Indian public sector especially at initial phase. The national assets should not be handed over to private sector at throw-away prices. The policies should be intervened in such a way that the policy of the disinvestment will not affect the last man of the country, adversely. So it is the need of the indian society to estimate the extent of loss to government in such cases and to suggest the appropriate remedies.